Ethosuximide and Phenytoin Dose-Dependently Attenuate Acute Nonconvulsive Seizures after Traumatic Brain Injury in Rats - Mountney, Andrea; Shear, Deborah A.; Potter, Brittney; Marcsisin, Sean R.; Sousa, Jason; Melendez, Victor; Tortella, Frank C.; Lu, Xi-Chun M. (Journal of neurotrauma, 2013)
Acute seizures frequently occur following severe traumatic brain injury (TBI) and have been associated with poor patient prognosis. Silent or nonconvulsive seizures (NCS) manifest in the absence of motor convulsion, can only be detected via continuous electroencephalographic (EEG) recordings, and are often unidentified and untreated. Identification of effective anti-epileptic drugs (AED) against post-traumatic NCS remains crucial to improve neurological outcome. Here, we assessed the anti-seizure profile of ethosuximide (ETX, 12.5-187.5 mg/kg) and phenytoin (PHT, 5-30 mg/kg) in a spontaneously occurring NCS model associated with penetrating ballistic-like brain injury (PBBI). Rats were divided between two drug cohorts, PHT or ETX, and randomly assigned to one of four doses or vehicle within each cohort. Following PBBI, NCS were detected by continuous EEG monitoring for 72 h post-injury. Drug efficacy was evaluated on NCS parameters of incidence, frequency, episode duration, total duration, and onset latency. Both PHT and ETX attenuated NCS in a dose-dependent manner. In vehicle-treated animals, 69-73% experienced NCS (averaging 9-10 episodes/rat) with average onset of NCS occurring at 30 h post-injury. Compared with control treatment, the two highest PHT and ETX doses significantly reduced NCS incidence to 13-40%, reduced NCS frequency (1.8-6.2 episodes/rat), and delayed seizure onset: <20% of treated animals exhibited NCS within the first 48 h. NCS durations were also dose-dependently mitigated. For the first time, we demonstrate that ETX and PHT are effective against spontaneously occurring NCS following PBBI, and suggest that these AEDs may be effective at treating post-traumatic NCS.